Radiation resistance of light-emitting diodes based on algaas-heterostructures to fast neutron and electron radiation; Известия вузов. Физика; Т. 57, № 12, ч. 3 - Rubanov P. V. Pavel Vladimirovich (2014, 2014)
Заглавие с экрана